Experimental Flexural Strength of Reinforced Beam and Reactive Powder Concrete with Bendrat Fiber - Lirawati, Lirawati (Universitas Pakuan, 2024)
Reactive powder concrete is a new type of concrete that has ultra-high compressive strength, the components of which are very fine powders that have high silica content. Reactive powder concrete has high compressive strength and ductility, which has the potential to replace steel materials in construction work, and has a very large opportunity for construction materials in Indonesia. In this study, 3 types of strength tests were carried out, namely compressive strength tests, splitting tensile tests and flexural strength tests. Compressive strength tests were carried out on cubes measuring 5 cm x 5 cm x 5 cm with cylinders measuring 10 cm x 20 cm, and splitting tensile strength on cylinders measuring 10 cm x 20 cm and flexural strength were carried out on reactive powder concrete measuring 4 x 6 x 60 cm and reinforced beams measuring 5 x 9 cm x 140 cm with the addition of 0.5% bendrat fiber from the concrete volume. The treatment of test objects for cubes and cylinders was carried out by curing with ordinary water. From the results of the tests that have been carried out, it was concluded that type II cement can increase the usual compressive strength of 43.9 MPa. For the splitting tensile strength of concrete using type II cement is 3.95 MPa higher than the use of type I cement of 2.23 MPa. The flexural strength of reactive powder concrete with 0.5% bendrat fiber is 23.44 MPa and reinforced concrete with 0.5% bendrat fiber is 61.93 MPa